176: EVIDENCE-BASED AND EFFECTIVE RESEARCH SKILLS OF IRANIAN MIDDLE SCHOOL STUDENTS. (8th February 2017) - Mostafaei, Helia; Sadeghi-Ghyassi, Fatemeh; Mostafaei, Hadi
Abstract : Background and aims: Recently, digital research is very popular in schools. The capacity of students to do an effective search is unclear which can lead to utilization of unacceptable evidence in their research. Aims: To evaluate middle school students' effective search skills. Methods: This survey was done during the summer school of Farzanegan talented students middle school. The self-administrated questionnaire studied 30 items about effective search and digital research skills of students. One hundred questionnaires were distributed in this summer school and students in the 7th and 8th grades filled the questionnaires. The administration of the questionnaire was counted as their concept. All data was analyzed at Excel 2013. Results: Eighty percent of students including 67.5% of the seventh and 32.5% of the eighth grade students responded to the questionnaires respectively. Shockingly, 96.2% of students only googled and most of them (73.7%) type the topic of their research in Persian to start their research strategy. More than half of them (52.5) believed the result of their search is mostly or always correct and 66.2% of them copy-pasted their findings without any assessment. Surprisingly, only 27.5% of them have proposed that they had problem with appraising the evidence. The best sources of the students for finding the answer of their questions were: Wikipedia, telegram, TV, books, E-Books, YouTube, classmates, Facebook and student information websites, and EBSCO, accordingly. 76.2% acknowledged that internet has turned students into copy machines. Only 31.2% agreed their teachers taught them how to do effective research. Conclusion: Most of the students were not familiar with valid sources of research evidence. Language barrier may limit their access to best evidence. Most students were not used to retrieving the evidence.